Formulation and Evaluation of Topical Gel Containing Nepalese Medicinal Plants - Gyawal, Rajendra; Aryal, Sadhana; Upreti, Bishal; Bhatta, Yub Raj; Yadav, Manish Kumar; Singh, Debendra; Shrestha, Joshna (Journal of Karnali Academy of Health Sciences, 2022)
Background: The formulation of herbal gel offers a great advantage in non-sticky products as compared to ointments and creams. Herbs are beneficial for human health containing several phytochemicals. Traditionally herbal preparations are used to enhance and facilitate the quality of the skin. Therefore, the aim of the present study was to prepare the herbal gel for the use of skin nourishing and help to cure skin related disease. Methods: Different crude drugs like Aloe (Aloe vera), Neem (Azadiracta indica), Turmeric (Curcuma longa),Onion (Allium cepa), and Basil (Ocimum tenuiflorum) are used to formulate the gel. Selection of these herbs are based on literature review on their individual uses in skin related problems. Formulation was developed from polymer base by experimental design based on previous works. Different compositions of herbs were designed for the formulation study. The water extract of the herb was prepared individually and later on mixed with the gel base ingredients containing carbopol 934, methylparaben and propyl paraben. The gel is subjected to evaluation of organoleptic properties and consistency, pH, and spreadability. Disk diffusion method was used to evaluate the antimicrobial property of the extract. DPPH method was used to determine the antioxidant property of extracts. Results: The average pH values of the formulations were 6.12 and 5.91, similarly spreadability of the two formulations F and S were 9.223 and 9.336 respectively. All the parameters were within the range. The antimicrobial study showed that both of the formulations have strong antimicrobial property to E.coli. Conclusion: The study concludes that the developed formulation of different concentrations are safe and within the range of standard. Therefore, we can say that our formulation product is one of the good natural gels which can be considered for the antioxidant benefit.